Forecasting recidivism in delinquency by intelligence and related constructs - Richter, Paul; Scheurer, Heinz; Barnett, Winfried; Kröber, Hans-Ludwig (Medicine, science and the law, 1996)
In a longitudinal survey of 122 healthy criminal offenders aged 18 to 37 years, the relationship between intelligence measured by the Wechsler Adult Intelligence Scale (WAIS), neuropsychological scales and delinquency was investigated. The Benton Test correlates well with the WAIS and moderately with offence data, but not with recidivism in delinquency. The 122 men had normal intelligence test scores (average IQ=102), but bad school and working records. The 34 per cent and 60 per cent respectively of offenders, who relapsed within the time span of 1.5 and 3 years respectively, showed significantly worse results in the Verbal Scale and in the Block Design of the Wechsler Intelligence Scale. Poor performance in the Information and the Block Design sub-tests of the WAIS, a low level of formal education and the belief in external control by circumstances and powerful others are predictors of a high risk of recidivism.